الصدمة النفسية للأم الفاقدة لابنها في حادث مرور - كروم الهام; بن مهية حليمة; سحيري زينب (My University, 2020)
The present study aims to reveal the level of psychological trauma of mothers who lost their children as a result of traffic accidents The target sample of this study are 3 cases of mothers who were interviewed with them we relied on a case study approach in each of the interviews we also used the PTSD scale of Davidson after making sure of its validity and reliability among the results are the presence of intense excitement for them : -Achieving the hypothesis of the study through the presence of psychological trauma for the mother who lost her son in a traffic accident as a result of the recurrence of the event, whether in dreams or in reality -A mother who has lost her son in a traffic accident has symptoms of hyper excitability